Role of asymptomatic and pre-symptomatic infections in covid-19 pandemic. (1st December 2021) - Gao, Wenjing; Lv, Jun; Pang, Yuanjie; Li, Li-Ming
Abstract : Liming Li and colleagues highlight the importance of identifying people without symptoms to control outbreaks of covid-19